Motion simulation and test on threshed grains in tapered threshing and transmission device for plot wheat breeding based on CFD-DEM - Dai, Fei; Song, Xuefeng; Zhao, Wuyun; Han, Zhengsheng; Zhang, Fengwei; Zhang, Shilin (International Journal of Agricultural and Biological Engineering, 2019)
Mechanization of field experiments is the only way to improve crop breeding and seed propagation effects. In order to further clarify and improve the working performance of tapered threshing device for plot breeding, and reduce the remaining seeds in the device, the numerical simulation was carried out on the motion process of materials in the longitudinal-axial tapered cylinder threshing and transmission device of the plot wheat breeding combine harvester based on CFD-DEM method. Simulation results showed that, threshing and transmission of particles and short stalks at axial direction could be realized under the influence of air flow. Meanwhile, the material transference and distribution rule and stream field distribution rule of air flow in the threshing and transmission device were obtained, the variations of velocity and displacement of particles and short stalks with time were obtained; the motion trajectories and forms of particles in different types of retention were also studied. At rotating speed of 1300-1600 r/min for the tapered threshing cylinder in the verification test, the particle retention rate in the enclosure was 0-0.13%, while in the simulation the particle retention rate in the enclosure was 0-0.11%, only a 0.02% difference between them. The results proved a favorable feasibility to simulate the working performance of the tapered threshing and transmission device for plot breeding through gas-solid coupling method.Keywords: particle threshing and transmission, tapered threshing and transmission device, hydromechanics calculation, discrete element, numerical simulation, testDOI: 10.25165/j.ijabe.20191201.4458Citation: Dai F, Song X F, Zhao W Y, Han Z S, Zhang F W, Zhang S L. Motion simulation and test on threshed grains in tapered threshing and transmission device for plot wheat breeding based on CFD-DEM. Int J Agric & Biol Eng, 2019; 12(1): 66–73.